On households and unemployment insurance - Sekyu Choi; Arnau Valladares-Esteban (Quantitative Economics, 2020)
We study unemployment insurance in a framework where the main source of heterogeneity among agents is the type of household they live in: some agents live alone while others live with their spouses as a family. Our exercise is motivated by the fact that married individuals can rely on spousal income to smooth labor market shocks, while singles cannot. We extend a version of the standard incomplete-markets model to include two-agent households and calibrate it to the US economy with special emphasis on matching differences in labor market transitions across gender and marital status as well as aggregate wealth moments. Our central finding is that changes to the current unemployment insurance program are valued differently by married and single households. In particular, a more generous unemployment insurance reduces the welfare of married households significantly more than that of singles and vice versa. We show that this result is driven by the amount of self-insurance existing in married households, and thus, we highlight the interplay between self- and government-provided insurance and its implication for policy.
Keywords: D91; E24; J64; J65; 330; Households; marriage; family; unemployment; unemployment insurance; worker flows; heterogeneous agents